Impact of Time Delay in a Forest biomass model in the Presence of Export and Industry - Kaur, Rajinder Pal (International Journal of Advanced Science and Technology, 2019)
In this paper, we have purposed and analyzed a delayed mathematical model of Forestry Resource Biomass with Industry and Export. In this model, we have studied the eﬀect of time delay on industrial technology in the context of conservation of biomass. The existence of equilibria and their local stability have been discussed in the absence of time delay. In the presence of time delay, the system exhibits rich dynamics with the existence of Hopf-bifurcation, period-doubling phenomenon, and chaos when parameter delaypassesthroughasequenceofintervals.Thestability anddirectionofthe bifurcating periodic solution is also determined using normal form theory and central manifold theorem. Finally, all analytical ﬁndings are validated using numerical simulation.